Exploring the vulnerability of practice-like activities: An ethnographic perspective - Yemisi Bolade-Ogunfodun; Matthew Sinnicks; Kleio Akrivou; Germán Scalzo (Frontiers in Sociology, 2022)
IntroductionThis paper explores the vulnerability of practice-like activities to institutional domination.MethodsThis paper offers an ethnographic case study of a UK-based engineering company in the aftermath of its acquisition, focusing in particular on its R&D unit.ResultsThe Lab struggled to maintain its practice-based work in an institutional environment that emphasized the pursuit of external goods.DiscussionWe use this case to develop two arguments. Firstly, we illustrate the concept of “practice-like” activities and explore their vulnerability to institutional domination. Secondly, in light of the style of management on display after the takeover, we offer further support to MacIntyre's critique of management. Finally, based on the empirical data we reflect on the importance of organizational culture, as well as friendship and the achievement of a common good in business organizations for these kinds of activities.